Medical navigation based on coloured markers for image-guided surgery - Elsamnah, Fahed; Sediono, Wahju (2013)
Image-guided surgery (IGS) is an advance medical navigation technology that enhances surgical operations and outcomes. The infrared markers have been used in the past years as references to visualize patient's body part, whether the markers are active or passive. This paper presents a new reference tool of tracking, and it develops a new algorithm of tracking an object in real time. Three coloured markers have been used as references of visualizing patient's body part whereas it provides many advantages, such as, unbounded objects tracking, inexpensive system comparing with IR-markers system, and unrestricted working area. This paper shows, that using coloured marker as a reference can be used to generate a good accuracy of visualization (RMS error 3.78mm) at the distance 1000 to 1300mm. Image filtering techniques have been used to process the images captured from stereo camera. As a result, medical navigation based on coloured markers contributes a promising result of image-guided surgery. Moreover, a fast algorithm for a real time tracking of coloured markers has been developed.